Cultural Integration in Science Education: Teachers’ Perceptions of The Sumbawa Oil (Melala) as Local Wisdom in Chemistry Learning - Riska Dia Sapitri; Nurlatifah Nurlatifah; Yunita Riskayanti (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Integrating local wisdom into chemistry education is crucial for creating a contextual and meaningful learning experience. This study analyses teachers’ perceptions of incorporating Sumbawa Oil (Melala) local wisdom into chemistry lessons in Sumbawa and West Sumbawa Regencies. Using a quantitative descriptive method, a Likert scale questionnaire was distributed via Google Forms. Results show that teachers’ perceptions generally fall within the good-to-excellent range, with the highest scores (90.2%) on relevance to curriculum and chemistry content. The significance test (Sig. 2-tailed) reveals no significant differences in perceptions across indicators or among teachers with different teaching experiences, indicating a consistently positive outlook on teaching with Melala local wisdom. The study emphasizes the importance of developing culture-based teaching tools and training. It encourages collaboration among schools, universities, and local governments to ensure the effective and sustainable integration of local wisdom.